Optimization of Ni–Co–Mn–Sn Heusler alloy composition for near room temperature magnetic cooling - Chen, X. (2014)
Ni–Co–Mn–Sn based Heusler alloys are promising magnetocaloric materials. The effect of both Co and Mn substitution in these alloys was studied. The magnetocaloric properties, thermopower, electrical resistivity, structural and magnetic phase transitions of Ni–Co–Mn–Sn alloys were determined. Interestingly, tuning Co and Mn composition resulted in high maximum entropy change (ΔSmax) of ∼32 J/kg K near room temperature in Ni48Co2Mn38Sn12 alloys. Alloying additions of cobalt increased magnetization and decreased the martensitic transition temperature (Ms). The Curie temperature of the austenite (TcA) and martensite (TcM) phases increased with increasing Co content. However, this decrease of Ms and increase of TcM resulted in decrease of the change in magnetization during the martensitic transition. Hence, Mn content was tuned to increase ΔSM and to tune Ms to a value relevant to room temperature applications. Thus, through tuning both Co and Mn composition, a high ΔSM was obtained near room temperature, making these alloys attractive magnetocaloric materials for room temperature applications.